Wild European Starlings (Sturnus vulgaris) Adjust to Captivity with Sustained Sympathetic Nervous System Drive and a Reduced Fight-or-Flight Response. - Romero, L. Michael.; Dickens, Molly J. (Tufts University. Tisch Library., 2016)
Although research on wild species typically involves capture, handling, and some degree of captivity, few studies examine how these actions affect and/or alter the animal's underlying stress physiology. Furthermore, we poorly understand the immediate changes that occur as wild animals adjust to captive conditions. Most studies to date have investigated relatively long-term changes in the glucocorticoid response to an acute stressor, but immediate changes in the fight-or-flight response are relatively understudied in wild-caught species. In this study, we investigated changes to the cardiovascular stress response during the first 10 d of captivity of freshly captured wild European starlings (Sturnus vulgaris) We demonstrated that (1) baseline heart rate (HR) remains elevated for several days following transport into captivity, (2) the normal balance between sympathetic nervous system (SNS) and parasympathetic nervous system regulation of HR is disrupted, with the SNS exerting relatively greater control over baseline HR for the first days of captivity, and (3) the HR response to startle, a mild stressor, becomes significantly reduced compared to that of starlings maintained in captivity for several months and remains below the control response for at least 10 d. These data are the first to show that successive acute stressors and introduction to a captive setting significantly alter the physiology and responsiveness of the cardiovascular stress response system.